Systematic Review of Research Trends in Environmental Literacy in Primary and Secondary Education: A Bibliometric Analysis 2016-2025 - Hanny Dwi Yonanda; Saiful Ridlo; Novi Ratna Dewi; Dyah Rini Indriyanti; Sri Ngabekti (Unnes Science Education Journal, 2026)
The latest Programme for International Student Assessment assesses competencies in the context of environmental issues, making the strengthening of environmental education crucial for enhancing students' environmental literacy. This study aims to analyze the trends, implementation, and dominant topics of environmental literacy in primary to secondary education. A systematic literature review (SLR) was conducted following the PRISMA protocol. A primary data search was performed on the Scopus database using the keyword "environmental literacy" for the 2016-2025 period, which yielded 22 journal articles that met the inclusion criteria. The analysis results show that environmental literacy is measured through four domains: knowledge, skills, attitudes, and responsible behavior. The most dominant measurement method was questionnaires, while the learning approaches included educational games, environmental projects, and problem-based models. The collaboration of activities, surveys, models, and learning media can enable the measurement of environmental literacy to fulfill its domains. Environmental literacy is increasingly oriented towards environmental education and environmental issues, considering effectiveness, awareness, behavior, and learning models. Effective implementation must integrate problem-based learning models that connect local environmental issues with indigenous wisdom, alongside interactive media and educational projects. This study contributes by emphasizing the balance between assessment and authentic learning experience for environmental literacy aligned with Programme for International Student Assessment competencies.